Analisis Efektivitas Pengendalian Piutang Tak Tertagih pada PT. Astra International TBK Periode 2020–2024 - Gitalis Natarina; Nurfahmi Nurfahmi; Resky Irfika; Faried Ma’ruf; Samirah Dunakhir; Alia Rezki Amalia (AKUNTANSI 45, 2025)
This study aims to analyze the effectiveness of uncollectible accounts receivable control at PT Astra International Tbk for the period 2020–2024. The research employs a descriptive method with a quantitative approach using financial ratios (delinquency ratio, collection ratio, and allowance adequacy ratio), as well as a qualitative approach by interpreting the ratio results in relation to the company’s internal control system. The data used are secondary data obtained from the company’s financial statements. The findings show that the delinquency ratio consistently decreased to below 1% over the last three years, reflecting the company’s success in minimizing bad debts. The collection ratio exceeded 99% and even reached 100% in 2022, indicating the effectiveness of its collection procedures. However, the allowance adequacy ratio revealed that the company set aside reserves significantly higher than the actual uncollectible receivables, sometimes 10–50 times greater, which demonstrates management’s prudence but may reduce resource efficiency. Overall, PT Astra International Tbk’s internal control system is considered effective in maintaining receivables quality and ensuring smooth cash flow, although the practice of excessive provisioning suggests inefficiency in resource allocation.